Tuning of fluorine content in graphene: towards large-scale production of stoichiometric fluorographene - Mazánek, Vlastimil; Jankovský, Ondřej; Luxa, Jan; Sedmidubský, David; Janoušek, Zbyněk; Šembera, Filip; Mikulics, Martin; Sofer, Zdeněk (Nanoscale, 2015)
The availability of well-defined modified graphene derivatives such as fluorographene, graphane, thiographene or hydroxygraphene is of pivotal importance for tuning the resulting material properties in numerous potential applications. A series of fluorinated graphene with various contents of fluorine was synthesized by a simple fluorination procedure in an autoclave with a nitrogen/fluorine atmosphere at different exposure times and temperatures. To investigate the composition, structure and properties all samples were characterized in detail by a number of analytical techniques such as SEM, XRD, EDS, AFM, STEM, combustible elemental analysis, STA, XPS, Raman spectroscopy, UV-VIS spectroscopy and cyclic voltammetry. The fully fluorinated graphene with the overall stoichiometry C1F1.05 had a bright white color indicating a significant change of band-gap. In comparison to other samples such a high concentration of fluorine led to the occurrence of exotic thermal behavior, strong luminescence in the visible spectral region and also the unique super-hydrophobic behavior observed on the material surface. The described tunable fluorination should pave the way to fluorographene based devices with tailored properties.